Implementasi Sertifikasi Halal dalam UU No. 33 Tahun 2014 dan UU No. 11 Tahun 2020: Perspektif Hukum dan Nilai-Nilai Studi Islam - Baidowi, Baidowi; Fitri, Nada Nabila Ayu (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Misinformation often occurs along with the change in authority to issue halal certificates from the Indonesian Ulema Council (MUI) to the Halal Product Assurance Management Agency (BPJPH) of the Indonesian Ministry of Religion. As a country with a Muslim majority population, of course the issue of halal product assurance is always a concern. In this article, the author intends to discuss and compare the halal certification process in Indonesia before the JPH Law, after the JPH Law and halal certification based on the Job Creation Law. The author considers it important to present this article with the hope that it can provide enlightenment to the public in understanding the halal certification process in Indonesia. This study uses a qualitative research method to describe the phenomena and discourse on the theme of this article. This study uses Pierre Bourdieu's genetic structuralism theory approach. Bourdieu introduced the concept of habitus which is an object of study in interpreting reality that is narrated repeatedly and seems to be the truth